Use of peripherally inserted central venous catheter in the Neonatal Intensive Care Unit of Instituto Nacional de Salud Del Niño Breña, 2017–2019 - Aguilar Ronceros, Lisset F. (2022)
Introduction. Currently the birth rate worldwide is 18.8% and in Peru it is 10%. The main causes of neonatal mortality are preterm births, infections and congenital defects. The neonatal intensive care unit is the area that is responsible for the care of newborns in critical condition, obtaining an adequate central venous access route for their treatment is essential. Objective. To describe the use of the percutaneous peripheral insertion catheter in the Neonatal Intensive Care Unit of the Instituto Nacional de Salud del Niño Breña, period June 2017 - June 2019. Methods. The study was descriptive, observational, retrospective, cross-sectional. The intentional sample was made up of approximately 110 medical records of newborns who were hospitalized in the neonatal intensive care unit. The technique the observation and the instrument the checklist. Results. 51.8% were neonates with surgical pathology. Likewise, 36.4% had a gestational age less than or equal to 32 weeks, the most used vein was the basilica with 27.3%, 37.3% of the catheters were removed due to suspected Sepsis and the tips were sent for culture. Conclusions. The care in the procedure and maintenance of the percutaneous catheter was adequate, presenting a low number of complications.